Prevalence of bullying, discrimination and sexual harassment in surgery in Australasia. Issue 12 (29th October 2015) - Crebbin, Wendy; Campbell, Graeme; Hillis, David A.; Watters, David A.
Abstract: Background: The topic of discrimination, bullying and sexual harassment in surgery was raised in the Australian media earlier in 2015. This led the Royal Australasian College of Surgeons (RACS) to commission an Expert Advisory Group to investigate and advise the College on their prevalence in surgery in Australia and New Zealand. This paper reports the findings with respect to prevalence of these inappropriate behaviours. Methods: The data in this paper were drawn from the published results of two quantitative surveys. One was an online survey sent to all RACS members. The other was an invited survey of hospitals, medical institutions and other related professional organizations including surgical societies. Results: The prevalence survey achieved a 47.8% response rate, representing 3516 individuals. Almost half of the respondents 1516 (49.2%) indicated that they had experienced one or more of the behaviours. This proportion was consistent across every specialty. Male surgical consultants were identified as the most likely perpetrators. More than 70% of the hospitals reported that they had instances in their organization of discrimination, bullying or sexual harassment by a surgeon within the last 5 years. Surgical directors or surgical consultants were by far the most frequently reported perpetrators (in 50% of hospitals). Conclusions: Discrimination, bullying and sexual harassment are common in surgical practice and training in Australia and New Zealand. RACS needs to urgently address these behaviours in surgery. This will involve a change in culture, more education for fellows and trainees, and better processes around complaints including support for those who have suffered.